1999
DOI: 10.1046/j.1365-294x.1999.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence and phylogeographic relationships among European perch (Perca fluviatilis) populations reflect glacial refugia and postglacial colonization

Abstract: We used the widely distributed freshwater fish, perch (Perca fluviatilis), to investigate the postglacial colonization routes of freshwater fishes in Europe. Genetic variability within and among drainages was assessed using mitochondrial DNA (mtDNA) D-loop sequencing and RAPD markers from 55 populations all over Europe as well as one Siberian population. High level of structuring for both markers was observed among drainages and regions, while little differentiation was seen within drainages and regions. Phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
276
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(299 citation statements)
references
References 56 publications
21
276
1
1
Order By: Relevance
“…Traces of imperfect tandem repeats were also observed in the L. elongatus D-loop sequences. These tandem repeats, typically found in the 5'-end or in the 3'-end of the D-loop segment, where the DNA replication initiates and ends, respectively (Lee et al, 1995;Nesbo et al, 1999), can be correlated to intra and inter-individual size variations in the D-loop region (Brzuzan, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Traces of imperfect tandem repeats were also observed in the L. elongatus D-loop sequences. These tandem repeats, typically found in the 5'-end or in the 3'-end of the D-loop segment, where the DNA replication initiates and ends, respectively (Lee et al, 1995;Nesbo et al, 1999), can be correlated to intra and inter-individual size variations in the D-loop region (Brzuzan, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…An ancient Danube-Elbe dispersal route was also supported by the fact that the Eger River population (originating from a tributary of the Elbe) grouped together with the SouthEuropean populations, two of which (Ram and Obr) originated from tributaries of the Danube (Figure 3). Although this connection has not been previously observed in grayling, other fish species inhabiting central and northern Europe have been argued to originate from their South-European conspecifics (Nesb et al, 1999;Englbrecht et al, 2000). Furthermore, the Danube-Elbe colonization route has been recently discussed to explain mtDNA haplotype patterns in bullhead, Cottus gobio (Englbrecht et al, 2000).…”
Section: Discussion Postglacial Dispersal Of T Thymallusmentioning
confidence: 96%
“…They showed that the species is subdivided into deeply divergent Western and Eastern phylogroups which are not, however, distinct species (Lajbner et al, 2010). Also in other freshwater species, including the chub (Leuciscus cephalus) (Durand et al, 1999), perch (Perca fluviatilis) (Nesbø et al, 1999) and barbel (Barbus barbus) (Kotlik and Berrebi, 2001), genetic lines related to the geographical location were observed which could indicate an evolutionary history common to different freshwater species. On the basis of the haplogroup composition, composite haplotype distribution and population location, it can be inferred that the haplogroup A observed in the present study corresponds to the Western phylogroup reported by Lajbner et al (2007 while the haplogroup B corresponds to the Eastern phylogroup.…”
Section: Discussionmentioning
confidence: 99%